Legal Analysis of Indonesian Regulation and Policy on Commitment to Achieving Net Zero Emission (NZE) in Renewable Energy Transition in Electricity Sector - Amalia, Nazwa; Napitupulu, Eunike Agalia; Ermanda, Imelia (Andalas Law Journal, 2024)
The community's need for energy is continuously increasing, especially for electricity. Indonesia's power generation is still largely dominated by non-renewable coal-based energy, which contributes significantly to greenhouse gas emissions. Although Indonesia has declared its commitment to Net Zero Emissions (NZE) by 2060, the existing legal framework remains inconsistent and often contradictory. This study aims to evaluate the regulatory and policy framework related to NZE in Indonesia’s electricity sector and to provide recommendations for improvement. Using normative legal research with a statute approach, this paper reveals contradictions between Indonesia’s international climate commitments and national regulations. It recommends harmonization of regulations and the development of alternative low-carbon energy sources such as nuclear power.